New Insights into Ring-In-Ring Complexes of [n]Cycloparaphenylenes including the [12]Carbon Nanobelt - Freiberger, Markus; Frühwald, Stefan; Minameyer, Martin; Görling, Andreas; Drewello, Thomas (Journal of Physical Chemistry A, 2023)
The supramolecular chemistry of cycloparaphenylenes (CPPs) is characterized by the ability of the ring system to undergo both concave and convex π-π interactions. As a consequence, ring-in-ring complexes can be formed in which the CPP serves as the host as well as the guest molecule ([n + x]CPP⊃[n]CPP). In this work, host-guest ring-in-ring complexes of [n]CPPs (n = 5-12) are investigated by means of electrospray ionization-tandem mass spectrometry (ESI-MS2) and laser desorption ionization mass spectrometry (LDI-MS). Extending the experimentally known complexes with ring size differences of five and six phenyl units (x = 5 and 6), we observe complexes with ring size differences of three up to seven phenyl units (x = 3-7). Energy-resolved collision experiments reveal that the charge is mainly located at the inner ring and complexes with phenyl unit differences of five and six are the most stable. In complexes featuring the same size difference, the complex stabilities slightly increase with an increasing size of the involved [n]CPPs. Utilizing the π-extended [12]carbon nanobelt ([12]CNB) as the guest also revealed an increase in complex stability. This study paves the way for a deeper understanding of the host-guest chemistry of CPPs.
CRIS-Team Scopus Importer:2023-12-08